Cluster analysis of nasal cytokines during rhinovirus infection identifies different immunophenotypes in both children and adults with allergic asthma. Issue 10 (6th June 2022) - Muehling, Lyndsey M.; Heymann, Peter W.; Carper, Holliday; Murphy, Deborah D.; Rajadhyaksha, Evan; Kennedy, Joshua; Early, Stephen V.; Soto‐Quiros, Manuel; Avila, Lydiana; Workman, Lisa; Platts‐Mills, Thomas A. E.; Woodfolk, Judith A.
Abstract: Background: Infection with rhinovirus (RV) is a major risk factor for disease exacerbations in patients with allergic asthma. This study analysed a broad set of cytokines in the noses of children and adults with asthma during RV infection in order to identify immunophenotypes that may link to virus‐induced episodes. Methods: Nasal wash specimens were analysed in children ( n = 279 [healthy, n = 125; stable asthma, n = 64; wheeze, n = 90], ages 2–12) who presented to a hospital emergency department, and in adults ( n = 44 [healthy, n = 13; asthma, n = 31], ages 18–38) who were experimentally infected with RV, including a subset who received anti‐IgE. Cytokines were measured by multiplex bead assay and data analysed by univariate and multivariate methods to test relationships to viral load, allergic status, airway inflammation, and clinical outcomes. Results: Analysis of a core set of 7 cytokines (IL‐6, CXCL8/IL‐8, IL‐15, EGF, G‐CSF, CXCL10/IP‐10 and CCL22/MDC) revealed higher levels in children with acute wheeze versus those with stable asthma or controls. Multivariate analysis identified two clusters that were enriched for acutely wheezing children; one displaying high viral load ("RV‐high") with robust secretion of CXCL10, and the other displaying high IgE with elevated EGF, CXCL8 and both eosinophil‐ and neutrophil‐derived mediators. Broader assessment of 39 cytokines confirmed that children with acute wheeze were not deficient in type 1 anti‐viral responses. Analysis of 18 nasal cytokines in adults with asthma who received RV challenge identified two clusters; one that was "RV‐high" and linked to robust induction of anti‐viral cytokines and anti‐IgE; and the other associated with more severe symptoms and a higher inflammatory state featuring eosinophil and neutrophil factors. Conclusions: The results confirm the presence of different immunophenotypes linked to parameters of airway disease in both children and adults with asthma who are infected with RV. Such discrepancies may reflect the ability to regulate anti‐viral responses. Abstract : Unsupervised analysis of nasal cytokines in children and adults with asthma during RV infection identified two distinct clusters associated with asthma; one defined by high viral load with increased production of specific anti‐viral mediators, and the other featuring high IgE and worse airway symptoms in the presence of a higher inflammatory state. These immunophenotypes may reflect differences in the ability to regulate anti‐viral responses in patients with asthma. Graphical abstract created with BioRender.com .